2010
DOI: 10.1002/app.31896
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of polyimide/multiwalled carbon nanotube (MWNT) nanocomposites by in situ polymerization and blending

Abstract: In this research, multiwalled carbon nanotube (MWNT) was oxidized and then modified to form carboxylic groups (ACOOH) on the surface and the end of the tube. After that, the MWNT was added to polyimide matrix to enhance its mechanical and electrical properties by in situ polymerization and blending. The PI/ MWNT composites were obtained by spin coating and multistep thermal curing process. The comparison of in situ polymerization and blending as well as the effect of unmodified and modified MWNT were discussed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…[2,3] Recently, PI/MWCNT nanocomposites with different PI matrices and compositions have been fabricated and investigated by a number of authors. [9][10][11][12][13][14][15][16][17] Rather different impacts of MWCNTs on PI properties have been observed depending on nanofiller content and functionalization, as well as the type of PIs and processing conditions. Through controlled variation of process parameters, various degrees of nanotube dispersion and distribution have been achieved.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…[2,3] Recently, PI/MWCNT nanocomposites with different PI matrices and compositions have been fabricated and investigated by a number of authors. [9][10][11][12][13][14][15][16][17] Rather different impacts of MWCNTs on PI properties have been observed depending on nanofiller content and functionalization, as well as the type of PIs and processing conditions. Through controlled variation of process parameters, various degrees of nanotube dispersion and distribution have been achieved.…”
Section: Introductionmentioning
confidence: 97%
“…For instance, Shlea et al [12] and Wu et al [13] showed how the controlled morphology affected the nanocomposite properties, and the MWCNT dispersion and distribution could be changed by adjusting processing conditions. As a result, a substantial increase (e.g., from 324 • C to 342 • C) and some decrease or no change in glass transition temperature, T g , were observed for the differently prepared PI/MWCNT nanocomposites; the latter negative effect was attributed to the presence of MWCNT agglomerates.…”
Section: Introductionmentioning
confidence: 98%
“…Carbon nanotubes have attracted much attention worldwide, because they have superior physical and chemical properties that are suitable for applications in hydrogen storage, chemical sensor, actuators, conductive tapes, tissue engineering, biomedical devices, and as nano‐reinforcement for composites . Carbon nanotubes–reinforced polymer nanocomposites are emerging as a new chemical technology in the processing of materials.…”
Section: Introductionmentioning
confidence: 99%
“…Polyimides (PIs) with good chemical resistance, superior thermal stability, and high mechanical strength are widely applied in electronic and aerospace industry 14–17. With the addition of single‐walled or multiwalled carbon nanotubes (SWNTs or MWNTs) in the PI matrix, the nanocomposites will have improved thermal conductivity, mechanical strength, electrical conductivity, and dielectric constant for advanced applications 4, 6–8, 15–26. Recently, Zhang et al8 reported an enhanced thermal conductivity of PI nanocomposite to 0.4 W/mK by incorporation of 5 wt % AlO(OH)‐coated MWNTs in PI matrix compared to 0.17 W/mK for pure PI.…”
Section: Introductionmentioning
confidence: 99%